dx | ||
∫ | ||
(x2+4x+8)3 |
1 | ||
∫ | dx | |
((x+2)2+4)3 |
x+2 | |
=t | |
2 |
1 | 1 | x | 2n−3 | 1 | |||||
∫ | dx = | + | ∫ | dx | |||||
(x2+1)n | 2n−2 | (x2+1)n−1 | 2n−2 | (x2+1)n−1 |
1 | 1 | 1 | t | 3 | 1 | |||||
∫ | dt = | + | ∫ | dt = | ||||||
4 | (t2+1)3 | 16 | (t2+1)2 | 16 | (t2+1)2 |
1 | t | 3 | t | 3 | 1 | |||||
= | + | + | ∫ | dt = | ||||||
16 | (t2+1)2 | 32 | t2+1 | 32 | t2+1 |
1 | t | 3 | t | 3 | ||||
= | + | + | arctgt+c | |||||
16 | (t2+1)2 | 32 | t2+1 | 32 |
1 | Ax+B | Cx+D | Ex + F | ||||
= | + | + | |||||
(x2+4x+8)3 | x2+4x+8 | (x2+4x+8)2 | (x2+4x+8)3 |
1 | a3x3+a2x2+a1x+a0 | |||
∫ | dx= | + | ||
(x2+4x+8)3 | (x2+4x+8)2 |
b1x+b0 | ||
∫ | dx | |
x2+4x+8 |